The genus Brechmorhoga Kirby, 1894, in the West Indies, with a proposed new status for Brechmorhoga archboldi (Donnelly) (Odonata; Libellulidae) - Meurgey, François (Zootaxa, 2016)
A revision of the species of Brechmorhoga from the Lesser Antilles includes Brechmorhoga archboldi (Donnelly, 1970) and Brechmorhoga praecox grenadensis Kirby, 1894. New distribution records are provided. Brechmorhoga archboldi is synonymized with B. praecox grenadensis. Figures, morphological characters of both sexes and the description of the female of B. p. grenadensis are given.